Optimizing E-SKCK Services for Intelkam Units in Increasing Public Satisfaction with SKCK Issuing in the Legal Area of the Bukittinggi Police - Shelin Angelina (Advances in Police Science Research Journal, 2021)
This research is motivated by technological advances that support the public service system, one of the service innovations is the E-SKCK service. However, there are still many people who do not understand what E-SKCK is and how to use it. These problems are poured into the formulation of problems that become the research material for researchers so that they can provide theoretical and practical benefits to researchers and readers. The literature review in this study consists of research literature taken from the results of previous research as well as conceptual literature that presents the theory of Organizational Resources and the theory of public services and the concept of Procedures for issuing SKCK and the concept of the community satisfaction index as an analytical tool. The literature review is part of a framework that describes the Optimization of E-SKCK Services for the Bukittinggi Police Intelligence Unit. The focus of this research is on Optimizing the E-SKCK Service of the Intelkam Unit in Increasing Community Satisfaction in the issuance of SKCK in the Bukittinggi Police Legal Area. The approach used by the researcher is the qualitative method. Furthermore, to obtain data, researchers used primary data sources obtained by means of interviews and observations and secondary sources obtained through document review. To determine the validity of the data, a triangulation technique was used which was then analyzed with 3 main elements, namely data reduction, data presentation and drawing conclusions. The results of the research and the discussion obtained in this study, the E-SKCK Service of the Bukittinggi Police Intelligence Unit aims to make it easier for the community to make SKCK. However, the E-SKCK service is still not optimal in its implementation. inhibiting factors for optimizing E-SKCK services include internal factors, networks, information systems and technology. With this, the Bukittinggi Police Intelligence Unit has not been able to realize excellent service in optimizing E-SKCK services. The researcher's suggestions in this study are to optimize the E-SKCK service of the Bukittinggi Police Intelligence Unit, eliminate the inhibiting factors for optimizing the E-SKCK service and socializing E-SKCK by utilizing print media or by direct socialization to the public.